Sucrose ingestion after exhaustive exercise accelerates liver, but not muscle glycogen repletion compared with glucose ingestion in trained athletes - Fuchs, C. J.; Gonzalez, J. T.; Beelen, M.; Cermak, N. M.; Smith, F. E.; Thelwall, P. E.; Taylor, R.; Trenell, M. I.; Stevenson, E. J.; van Loon, L. J. (Journal of Applied Physiology, 2016)
The purpose of this study was to assess the effects of sucrose vs. glucose ingestion on postexercise liver and muscle glycogen repletion. Fifteen well-trained male cyclists completed two test days. Each test day started with glycogen-depleting exercise, followed by 5 h of recovery, during which subjects ingested 1.5 g/kg·h sucrose or glucose. Blood was sampled frequently and 13C magnetic resonance spectroscopy and imaging were employed 0, 120, and 300 min postexercise to determine liver and muscle glycogen concentrations and liver volume. Results were as follows: Postexercise muscle glycogen concentrations increased significantly from 85 ± 27 (SD) vs. 86 ± 35 mmol/l to 140 ± 23 vs. 136 ± 26 mmol/l following sucrose and glucose ingestion, respectively (no differences between treatments: P = 0.673). Postexercise liver glycogen concentrations increased significantly from 183 ± 47 vs. 167 ± 65 mmol/l to 280 ± 72 vs. 234 ± 81 mmol/l following sucrose and glucose ingestion, respectively (time × treatment, P = 0.051). Liver volume increased significantly over the 300-min period after sucrose ingestion only (time × treatment, P = 0.001). As a result, total liver glycogen content increased during postexercise recovery to a greater extent in the sucrose treatment (from 53.6 ± 16.2 to 86.8 ± 29.0 g) compared with the glucose treatment (49.3 ± 25.5 to 65.7 ± 27.1 g; time × treatment, P < 0.001), equating to a 3.4 g/h (95% confidence interval: 1.6-5.1 g/h) greater repletion rate with sucrose vs. glucose ingestion. In conclusion, sucrose ingestion (1.5 g·kg-1·h-1) further accelerates postexercise liver, but not muscle glycogen repletion compared with glucose ingestion in trained athletes.